Eksplorasi Pelaksanaan Tupoksi KUA Medan Kota Dalam Sosialisasi Kepada Masyarakat - Syahminan Syahminan; Mhd Fajar Fadhillah; Dwi Maulia Arifa; Nadya Putri Utami Pane; Hijriyah Hijriyah; M. Naufal Aulia Zein; Rahmad Hidayah Pulungan (LPPI UMN AL WASHLIYAH, 2025)
The Office of Religious Affairs (KUA) has the primary duty and function of providing religious services to the community, including matters related to marriage, religious guidance, and the dissemination of Islamic policies. This article aims to analyze the implementation of the main duties and functions (Tupoksi) of KUA Medan Kota in conducting socialization efforts within the community. The research method used is a qualitative approach, with data collection techniques including interviews, observations, and document studies. The findings indicate that KUA Medan Kota is actively engaged in socialization efforts through various programs, such as premarital counseling, religious outreach, and Islamic legal awareness initiatives.